Task-concurrent anodal tDCS modulates bilateral plasticity in the human suprahyoid motor cortex - Zhao, Shaofeng; Dou, Zulin; Wei, Xiaomei; Li, Jin; Dai, Meng; Wang, Yujue; Yang, Qinglu; He, Huai (Frontiers in Human Neuroscience, 2015)
Transcranial direct current stimulation (tDCS) is a non-invasive method to modulate cortical excitability in humans. Here, we examined the effects of anodal tDCS on suprahyoid motor evoked potentials (MEP) when applied over the hemisphere with stronger and weaker suprahyoid/submental projections, respectively, while study participants performed a swallowing task. 30 healthy volunteers were invited to two experimental sessions and randomly assigned to one of two different groups. While in the first group stimulation was targeted over the hemisphere with stronger suprahyoid projections, the second group received stimulation over the weaker suprahyoid projections. tDCS was applied either as anodal or sham stimulation in a random cross-over design. Suprahyoid MEPs were assessed immediately before intervention, as well as 5, 30, 60, and 90 min after discontinuation of stimulation from both the stimulated and non-stimulated contralateral hemisphere. We found that anodal tDCS (a-tDCS) had long-lasting effects on suprahyoid MEPs on the stimulated side in both groups (tDCS targeting the stronger projections: F(1,14) = 96.2, p < 0.001; tDCS targeting the weaker projections: F(1,14) = 37.45, p < 0.001). While MEPs did not increase when elicited from the non-targeted hemisphere after stimulation of the stronger projections (F(1,14) = 0.69, p = 0.42), we found increased MEPs elicited from the non-targeted hemisphere after stimulating the weaker projections (at time points 30 to 90 min) (F(1,14) = 18.26, p = 0.001). We conclude that anodal tDCS has differential effects on suprahyoid MEPs elicited from the targeted and non-targeted hemisphere depending on the site of stimulation. This finding may be important for the application of a-tDCS in patients with dysphagia, for example after stroke.